Internet-Administered Emotional Awareness and Expression Therapy for Somatic Symptom Disorder With Centralized Symptoms: A Preliminary Efficacy Trial - Maroti, Daniel; Ek, Josefine; Widlund, Rose-Marie; Schubiner, Howard; Lumley, Mark A.; Lilliengren, Peter; Bileviciute-Ljungar, Indre; Ljótsson, Brjánn; Johansson, Robert (Frontiers in Psychiatry, 2021)
Background: There is growing evidence that trauma, psychosocial conflict, and difficulties with emotional processing contribute to centralized somatic symptoms. Emotional Awareness and Expression Therapy (EAET) was developed to address these factors and reduce symptoms, and EAET has shown efficacy in face-to-face formats. No trial of an internet-delivered EAET (I-EAET) exists, however, so we developed such an intervention and conducted an uncontrolled feasibility and potential efficacy trial of I-EAET for patients with Somatic Symptom Disorder (SSD) with centralized symptoms (SSD-CS). Method: After screening potential participants, a sample of 52 patients (50 women, two men; age M = 49.6, SD = 11.9) diagnosed with SSD-CS initiated treatment. I-EAET consisted of nine weekly modules focused on psychoeducation, emotional awareness and exposure, and anxiety regulation with self-compassion. Therapists communicated with each patient by email for about 20 min per week during treatment, answering questions and giving feedback on homework assignments. Patients completed measures of somatic symptoms, depression, anxiety, trauma-related symptoms, and functional disability before treatment and again at post-treatment and 4-month follow-up. Results: A large reduction in somatic symptoms (PHQ-15) occurred pre-to post-treatment (d = 1.13; 95% CI: 0.84–1.47) which was fully maintained at 4-month follow-up (d = 1.19; 95% CI: 0.88–1.56). Twenty-three percent of the patients at post-treatment and 27% at follow-up achieved a 50% or greater reduction in somatic symptoms, and about 70% achieved a minimally important clinical difference. In addition, at post-treatment, there were small to medium reductions (d's from 0.33 to 0.72) in anxiety (GAD-7), depression (PHQ-9), trauma-related symptoms (PCL-5), and functional disability (Sheehan Disability Scale). For all of these secondary outcomes, improvements were slightly to substantially larger at follow-up than at post-treatment (d's from 0.46 to 0.80). Conclusion: I-EAET appears to be a feasible treatment for adults with SSD and centralized symptoms, resulting in substantial and durable improvement not only in somatic symptoms but in other psychiatric symptoms and functioning. Controlled trials are needed determine the effects of I-EAET specifically and how this approach compares to face-to-face EAET and to other internet-delivered treatments, such as cognitive-behavioral interventions. Research should also identify treatment responders and mechanisms of change in EAET. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04122846.